Guillain-Barré Syndrome associated with SARS-CoV-2 infection. (2020) - Virani, Ahmed; Rabold, Erica; Hanson, Taylor; Haag, Aaron; Elrufay, Rawiya; Cheema, Tariq; Balaan, Marvin; Bhanot, Nitin
Abstract: We present a case of Guillain- Barré Syndrome (GBS) in a patient with confirmed COVID-19 infection. GBS in commonly encountered after an antecedent trigger, most commonly an infection. To date, only one case of GBS associated with this infection has been described. Clinicians should consider this entity since it may warrant appropriate isolation precautions especially in a patient who may not present primarily with typical constitutional and respiratory symptoms associated with COVID-19.